ASAS RES JUDICATA PRO VERITATE HABETUR DALAM PENINJAUAN KEMBALI TERHADAP PUTUSAN LEPAS DARI SEGALA TUNTUTAN HUKUM OLEH JAKSA PENUNTUT UMUM - Pinatih, Ngurah Ketut Widhi Aditya (Justitia et Pax, 2024)
This paper discusses the implementation of the principle of res judicata pro veritate habetur in the review of acquittal by the Public Prosecutor which examines the procedural law in criminal justice in Indonesia. Judicial review is essentially an extraordinary legal remedy granted as the right of a convicted person or his heirs against a court decision that is considered unfair. However, in its implementation in Indonesia, there are several cases that are considered controversial. Djoko Tjandra (2009) and Hartono (2022) are victims of judicial review by public prosecutors who filed on the basis of authority granted by law, namely Article 263 paragraph (3) of the Criminal Procedure Code, Article 24 of the Judicial Power Act, and Article 30C of the Prosecutor's Office Act. This paper will further examine the application of the principle of res judicata pro veritate habetur in criminal justice to acquittals. The research method used is library research, which is research that uses library sources to obtain data for this research. By using a case approach method that examines legal norms or rules in legal practice related to the principle of res judicata pro veritate habetur with the aim of creating justice and certainty. From the results of the author's research conclude that exceptions to the principle of res judicata pro veritate habetur are only given to convicts or their heirs.